2010
DOI: 10.1143/jpsj.79.044705
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ab initio Low-Energy Models for LaFePO, LaFeAsO, BaFe2As2, LiFeAs, FeSe, and FeTe: Electron Correlation and Covalency

Abstract: Effective low-energy Hamiltonians for several different families of iron-based superconductors are compared after deriving them from the downfolding scheme based on first-principles calculations. Systematic dependences of the derived model parameters on the families are elucidated, many of which are understood from the systematic variation of the covalency between Fe-3d and pnictogen-/chalcogenp orbitals. First, LaFePO, LaFeAsO (1111), BaFe 2 As 2 (122), LiFeAs (111), FeSe, and FeTe (11) have overall similar b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

49
376
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 344 publications
(427 citation statements)
references
References 88 publications
(137 reference statements)
49
376
2
Order By: Relevance
“…It should be noted that, depletion of these states from the near E F clearly indicates an opening up of a pseudogap as the temperature is lowered from 300 K to 77 K. Figure 2(a) shows the calculated total density of states (DOS) over the valence band region. The calculated DOS matches with the earlier theoretical study [21,22] and also with the observed experimental data. Fig 2) corresponds to the experimentally obtained features at 0.1 eV and 0.5 eV, respectively.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It should be noted that, depletion of these states from the near E F clearly indicates an opening up of a pseudogap as the temperature is lowered from 300 K to 77 K. Figure 2(a) shows the calculated total density of states (DOS) over the valence band region. The calculated DOS matches with the earlier theoretical study [21,22] and also with the observed experimental data. Fig 2) corresponds to the experimentally obtained features at 0.1 eV and 0.5 eV, respectively.…”
Section: Resultssupporting
confidence: 89%
“…Peak C at 4 eV is due to the hybridized Fe 3d -Se 4p/Te 5p states while D at 6 eV corresponds to Se 4p/Te 5p states. Our calculations based on the TBLMTO-ASA (fig 2(a)) and also other's calculations [21,22] conform to these assignments. The sharp feature A seen in the case of FeSe transforms into a broadened one for FeTe.…”
Section: Resultssupporting
confidence: 86%
“…From the first-principles downfolding scheme given by the cRPA method, Ref. 46 revealed that U ll , U ll ′ , J ll ′ , J ll ′ in H dd are orbital-dependent and that the average of U ll isŪ d = 7.2 eV for FeSe.…”
Section: Dynamical Mean Field Theorymentioning
confidence: 99%
“…46. We use the exact diagonalization method for a finite-size cluster as an impurity solver to obtain the local quantities such as the self-energy, which is calculated at T = 0 as the explicit T -dependence is expected to be small in the intermediate correlation regime with Z > ∼ 0.5.…”
Section: Dynamical Mean Field Theorymentioning
confidence: 99%
See 1 more Smart Citation